Pulse pressure in patients with arterial hypertension in Slovenia - Pal, Marjetka; Pajntar, Marjan; Leskošek Brane; Drinovec, Jože; Ferk, Polonca (Acta Medico-Biotechnica, 2021)
Purpose: The aim of our study was to evaluate age- and gender-dependent pulse pressure (PP), systolic blood pressure (SBP), and diastolic blood pressure (DBP) distributions as well as their interconnected relationships in a large patient sample diagnosed with arterial hypertension in Slovenia. Methods: Data on brachial arterial pressure measurements (SBP, DBP) were taken from the medical records of 19,972 arterial hypertension patients. More than 360 family medicine physicians participated in the study. The majority of the data was collected from 2002 to 2006. Results: Mean PP, SBP and DBP were (71.2 ± 16.9) mmHg, (172.8 ± 18.1) mmHg and (101.6 ± 10.4) mmHg, respectively. Linear regression analysis showed a significant association of PP with age (p < 0.001) and with gender (p < 0.001). Pulse pressure increased similarly with age for men and women. Women had significantly higher PP than men during ages of 35 to 65 years (p < 0.001), but the difference was less evident for those above 80 years. Pulse pressure had a U-shape-like relationship with DBP, and a strong, almost linear relationship with SBP. Conclusion: The results of our study show age- and gender-dependent differences in PP distribution for Slovene patients with arterial hypertension. These findings may remind family medicine physicians to take PP values into consideration when planning antihypertensive therapy.